Energy management of renewable energy-based microgrid system with HESS for various operation modes - Kumar, G. V. Brahmendra; Palanisamy, K. (Frontiers in Energy Research, 2022)
This paper proposes a ramp-rate control approach for a grid-connected MG with a hybrid energy storage system. Distributed energy sources (DERs), such as solar photovoltaic (PV) and wind, combined with energy storage (ES) and controllable loads, are critical to a power grid that can handle the intermittent nature of renewable energy sources. Therefore, the complexity of the system is increasing as researchers move towards a more renewable based power grid. An energy management system (EMS) for microgrids must consider the power available in RESs as well as the storage capacity of energy storage devices (ESSs). Modern MGs include a wide range of converters for a variety of applications, including distributed generation interconnection, grid integration, energy storage management systems, and demand management, among others. So, the ramp-rate control smooths fluctuations in photovoltaic power, which increases system reliability. In the proposed system, 80 V DC is used to supply high and low power DC loads. The suggested system can extract the maximum amount of energy from RESs, maintain efficient ESS management, and achieves quick DC-link voltage regulation with settling time of 230 ms throughout all operating modes. These conditions are met by the energy management system, which gives the MG with operational capability and ensures its reliability. The MG with proposed features and EMS was validated using the MATLAB/Simulink environment, and results were obtained using the Hardware-in-the-Loop (HIL) experimental test bench. The proposed small-scale RES-based MG can be used to develop and test algorithms for a wide range of MG applications.